Kualitas Pelayanan Kesehatan Di Puskesman Mulyojati Kota Metro (The Quality of Health Care Services at Mulyojati Public Health Center in Metro City) - I Wayan Lendra (PUBLICA, 2011)
Health Care Service is one of the citizenâs basic needs that must be properly fulfilled by the state. It is stated in Indonesia Constitution dan Laws. Therefore, the state that represented by governmentÂ  must give high public health qualities to the citizens. The Mulyojati Public Health Center (Puskesmas Mulyojati) Metro City has given the good quality in public health services to the customers, at least in 5 aspecs i.e: tangibility, competence, politeness, communication and serviceâs procedures. But, there are some things that should be improved by official i.e: the facilities, servant attitude both medic and paramedic and personal quantity. Generally, public health service at Mulyojati Health Center has fulfilled the minimum requirement of quality public service.